(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless networks are computer networks that are not connected by cables of any kind which enables enterprises to avoid the costly process of introducing cables. Ad hoc wireless communication between devices might be loosely defined as a scheme, often referred to as ad hoc networking. MANET is a type of ad hoc network that has the characteristics of mobility and self-configuring in which each mobile node not only act as a host and it also act as a router. Each node operates with the limited battery power to forward the data packets from the source to a group of the nodes. In a MANET, multicast is a very useful communication system for group-oriented applications, where one-to-many propagations are needed frequently in critical situations. This paper presents a new power-aware multicasting algorithm for MANETs. Here, it uses the residual battery energy for the multicasting from the source to a group of destinations. These networks are lack of fixed infrastructure and nodes are typically powered by batteries with a limited energy supply where in each node stops functioning when the battery drains. Multi-casting procedures for routing in MANET become a major concern to support the propagation of data from a sender to all the receivers. Hence the system propose PUMA (Protocol for Unified Multicasting through Announcements) for performing multi-cast routing. It reduces the load on wireless nodes by selecting the route with minimum energy with maximum hop count within the multicast group. Simulation results show that the performance of the proposed protocol is increased than the existing protocol in terms of throughput, delay, PDR and network lifetime.